Filantropi Pada Masyarakat Multikultural (Studi Kasus di Desa Klepu Kec. Sooko Kab. Ponorogo) (ZISWAF: Jurnal Zakat dan Wakaf, 2020)
Ponorogo is a district that has many faith-based philanthropic institutions. One of them is Klepu Village, Sooko Subdistrict which is the oldest village of Christianity but the majority of the population is Muslim. Klepu Village as the central target of various institutions engaged in religious based philanthropy, both Islam and Christianity. The research was conducted, first, by different institutions with the same object; second, on the philanthropic institution in the midst of a multicultural society; third, by various institutions lives harmony in the community. In addition, this research also aimed to find out how fundraising activity is carried out for the sustainability of each institution's program. Religious-based philanthropic institutions cannot be separated from supporting and inhibiting factors. Supporting factors include the values of religiosity, awareness, support, commitment, dedication, and community participation to realize philanthropic programs without any clash between existing philanthropic institutions. Meanwhile, they face the same inhibiting factors that is limited funds to raised their program. Referring to the study findings, it can be concluded that the philanthropic program shown by religious-based philanthropic institutions, namely Islamic Religious Instructor, BMH, and DPP, are included in traditional philantrophy which approach is to fulfill the basic needs (food, clothing, health and education). While social justice philanthropy becomes the orientation of the Ministry of Religion, Islamic Extension Workers, and LMI, which focus on assistancing to empower people to have a long-term impact. With these two philanthropic models, the resulting impact is harmony living and economic independence in the multicultural Klepu society.